Kontribusi Usaha Penambangan Pasir Laut Pada Kesejahteraan Nelayan di Desa Labone Kecamatan Lasalepa Kabupaten Muna - Hendri, Hendri; Yusria, Wa Ode; Fyka, Samsul Alam (Department of Agribusiness, Halu Oleo University, 2019)
This study aims to determine the contribution of sea sand mining to the income of fishing families, and the welfare level of fishermen in Labone Village, Lasalepa District, Muna Regency. This research was conducted in July-April 2019. The variables measured in this study include: the identity of respondents include: age, education level, number of dependents, mining of sand experience.Â The level of welfare includes: income, production, revenue, while the observed variables to see the income of the sand mining community include: production, production costs, prices, and revenues. Analysis of the data used, namely: income analysis, the level of welfare of fisherman households is measured by using indicators from the Provincial Minimum Wage (UMP). The results showed that: 1) The contribution of sea sand mining to the income of the fishermen's family was 97.12 percent which means that the contribution was very large, and 2) The welfare level of fishermen in Labone Village, Muna Regency, Southeast Sulawesi Province was in the prosperous category based on line indicators poverty in the Southeast Sulawesi Province UMP in 2018